The environmental psychology of prisons and jails : creating humane spaces in secure settings - Wener, Richard (Cambridge : Cambridge University Press, 2012)
'It is often a curious experience for me to lecture about design and behavior in correctional settings because of the different groups of people with different kinds of expertise who may be in the audience. When I am speaking to Criminal Justice/Corrections professionals some of the concepts I discuss are well known (such as the history of prisons, the direct supervision system of design and management, the nature of prison crowding and isolation) but much of the psychology, especially environmental psychology -- including research methodology, stress, post occupancy evaluation, personal space and territoriality, psychology of crowding -- is not. If I speak to psychologists just the opposite is true, and a meeting of architects presents a different set of competencies entirely. So it is with this book. Some topics will be well-known to corrections people, others to psychologists, and still different ones for designers. The hard part is always in figuring out which elements of familiarity can be assumed and which need deeper background. I hope that parts of this book will be of interest to all of those groups -- as well as others such as policy makers'--
Includes bibliographical references and index.
Keywords: Environmental psychology; Prisons; Jails; Correctional institutions